Causality Implications of Unemployment, Inflation, and Poverty in Indonesia - Dea Rustami; BIE Indraswanti; Mery Anitasari; Lela Rospida (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to analyze the causal relationship between unemployment, inflation, and poverty in Indonesia. The research methodology employed Granger causality test and time series regression analysis. The findings indicate a one-way causal relationship between the variables of unemployment and poverty. Specifically, unemployment has been shown to affect the level of poverty in Indonesia. Furthermore, the study also identifies a one-way causal relationship between the variables of poverty and inflation.